The Lovisa stratiform Zn-Pb deposit, Bergslagen, Sweden : Structure, stratigraphy, and ore genesis - Jansson, Nils; Sädbom, Stefan; Allen, Rodney; Billström, Kjell; Spry, Paul G (Economic Geology, 2018)
Medium- to high-grade metamorphosed, 1.9 Ga, stratiform, syngenetic Zn-Pb±Ag sulfide deposits comprise an economically important type of ore deposit in the Bergslagen lithotectonic unit of the Fennoscandian shield. The Lovisa Zn-Pb deposit occurs in a metamorphosed succession of rhyolitic ash-siltstone, rhyolitic mass flow deposits, limestone and iron formation, deposited at a stage of waning volcanism in Bergslagen. Accessory graphite, absence of Ce anomalies in shale-normalized rare-earth element (REE) data, and absence of hematite in Mn-rich iron formations stratigraphically below the Lovisa Zn-Pb deposit indicate a suboxic-anoxic depositional environment. The uppermost Mn-rich iron formation contains disseminated, inferred syngenetic Pb-Ag mineralization with mainly negative δ34S values in sphalerite and galena (-6.1 to -1.9‰). Deposition of this iron formation terminated during a pulse of explosive felsic volcanism. The Lovisa Zn-Pb deposit is interpreted to have formed in an alkali-rich brine pool developed immediately after this volcanic event, based on lithogeochemical and stratigraphic evidence. The first stage of mineralization deposited stratiform sphalerite mineralization with mainly positive δ34S values (-0.9 to +4.7‰). This was succeeded by deposition of more sphalerite-galena stratiform mineralization with δ34S values close to 0‰ (-2.1 to +1.5‰). The more galena-rich mineralization partitioned strain and was partly remobilized during later ductile deformation. The stratigraphic context, sulfide mineralogy, sulfur isotopes and alteration geochemistry suggest that the metalliferous fluids and the depositional environment were H2S-deficient (S-poor or SO42--dominant). The source of sulfur is interpreted to have been a mixture of H2S derived from bacterial and thermochemical seawater sulfate reduction, and sulfur derived from leaching of volcanic rocks, with the latter becoming more important over time. Lovisa formed in a setting where basin subsidence was periodically punctuated by the deposition of ...